Association of Soluble B7-H4 and Circulating Tumor Cells in Blood of Advanced Epithelial Ovarian Cancer Patients - Mach, Pawel; Kimmig, Rainer; Kasimir-Bauer, Sabine; Buderath, Paul (Frontiers in Oncology, 2021)
Introduction: Epithelial ovarian cancer (EOC) is the deadliest gynecologic malignancy worldwide. Reliable predictive biomarkers are urgently needed to estimate the risk of relapse and to improve treatment management. Soluble immune-checkpoints in EOC are promising molecules serving as prognostic biomarkers accessible via liquid biopsy. We thus, aimed at elucidating the role of sB7-H4 in EOC. Material and methods: We analyzed soluble serum B7-H4 (sB7-H4) using ELISA and circulating tumor cells (CTCs) in blood applying the AdnaTest OvarianCancer in 85 patients suffering from advanced EOC. Findings were correlated with clinical parameters as well as survival data. Results: sB7-H4 was detectable in 14.1% patients, CTCs in 32.9% patients and simultaneous presence of CTCs and sB7-H4 was found in 7% patients, respectively. Although no association between sB7-H4 and CTC could be documented, each of them served as independent predictive factors for overall survival (OS). Conclusion: sB7-H4 and CTCs are independent prognostic biomarkers for impaired survival in EOC. As they are easily accessible via liquid biopsy, they may be of potential benefit for the prediction of therapy response and survival for EOC patients.